Energy Efficiency Optimization of Finite Block Length Star-Ris-Aided Mu-Mimo Broadcast Channels - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Schober, Robert; Hanzo, Lajos (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2025)
Energy-efficient designs are proposed for multi-user (MU) multiple-input multiple-output (MIMO) broadcast channels (BC), assisted by simultaneously transmitting and reflecting (STAR) reconfigurable intelligent surfaces (RIS) operating at finite block length (FBL). In particular, we maximize the sum energy efficiency (EE), showing that STAR-RIS can substantially enhance it. Our findings demonstrate that the gains of employing STAR-RIS increase when the codeword length and the maximum tolerable bit error rate decrease, meaning that a STAR-RIS is more energy efficient in a system with more stringent latency and reliability requirements.
CRIS-Team Scopus Importer:2025-10-03
Keywords: Energy efficiency; finite block length; MIMO broadcast channels; optimization; resource allocation; STAR-RIS